Clinical Outcomes of Liver Transplantation in Patients With Hepatorenal Syndrome: A Single Center Study in China - Li, Fangcong; Wang, Tielong; Zhan, Liqiang; Jia, Zehua; Luo, Tao; Chen, Shirui; Zhao, Qiang; Guo, Zhiyong; He, Xiaoshun; Wang, Dongping (Frontiers in Surgery, 2022)
Background: Liver transplantation (LT) is an optimal treatment for hepatorenal syndrome (HRS) patients but the renal function recovered is not universal after operation. The aim of study is to explore the association between stages of hepatorenal syndrome – acute kidney injury (HRS-AKI) and incidence of post-operation chronic kidney disease (CKD). Methods: Data of HRS-AKI patients received LT were collected from the First Affiliated Hospital of Sun Yat-sen University from 2016 to 2020. A survival and incidence curve and multivariable model were established to analyze the impacts of HRS-AKI stages and variables on 90-day survival and CKD within 12 months. Results: 62 HRS-AKI patients were enrolled in this study. Patients diagnosed as Stage 1, 2 and 3 were 35 (57%), 17 (27%) and 10 (16%), respectively. The patients at Stage 3 had the poorest outcomes with the lowest rate of 90-day survival and the highest incidence of CKD in 12 months among all patients. Stage 3 (SHR = 6.996, 95% CI, 1.556 – 31.446) and postoperative renal replacement therapy (RRT) (SHR = 3.106, 95% CI, 1.072 – 9.000) were found as the useful indicators for poor prognosis. Conclusions: In our study, the classification of HRS-AKI stages can be used to predict the prognosis of HRS patients after LT. The peak serum creatinine level is a risky predictor in high HRS-AKI stages patients.